FUNGSI TRAFFIC ACCIDENT RESEARCH CENTRE UNTUK MENDUKUNG PROGRAM KESELAMATAN BERLALULINTAS - Muhammad Tito Karnavian (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2018)
Road safety is the crisis condition in developing countries such as Indonesia. Based on 2016 data, the dead tolls of road accidents were 26,000, or 10.9 fatalities per 100,000 inhabitants. The majority of victims was between 15 and 29 years old (IRSMS, 2016). This condition shows the human capital lost caused by many dead prematurely on road. The Long Term National Road Safety Plan (RUNK) declareted in 2011 has the main goal is reducing road fatalities by 50% and 80% in 2020 and 2035 respectively. Indonesia National Police (INP) has the main role to coordinate and realize safer road users in the RUNK. Integrated Road Safety Management System (IRSMS) is the road accident data- based application that was developed by INP and it must be the evidence based for decision policies and development action plan activities. Establishment of Traffic Accident Research Centre (TARC) has the main objective to sinergising Indonesia traffic police with academia and researcher to carry out in depth study as well as to develop programmes that able both structural and cultural to construct safety concern society. INP understands that enforcement program solely cannot solve road safety problem. It recognizes that achievement is not possible without understanding the problems and incorporation with all stakeholders in road safety. Keselamatan di jalan raya adalah sesuatu hal yang kritis di negara berkembang seperti Indonesia. Data kecelakaan pada tahun 2016 menunjukan 26.000 orang, 41.9 orang per 100.000 penduduk meninggal di jalan raya dimana mayoritas korban berusian 15 – 29 (IRSMS, 2016). Kondisi memperlihatkan kehilangan negara atas aset sumber daya yang dimiliki. Rencana Umum Nasional Keselamatan (RUNK) pada tahun 2011bertujuan menurunkan fatalitas di jalan raya. POLRI mempunyai peran utama dalam mengkoordinasi dan menciptakan pengguna jalan yang berkeselamatan. Integrated Road Safety Management System (IRSMS) adalah aplikasi pencatatan data kecelakaan yang dikembangkan oleh POLRI harus dijadikan basis pengambilan keputusan dan aktifitas kampanye keselamatan di jalan raya. Pendirian Traffic Accident Research Centre (TARC) bertujuan menciptakan sinergitas antara KORLANTAS POLRI dan akademisi dalam melakukan in-depth study serta. Penciptaan program yang mampu secara struktur dan kultur menciptakan masyarakat yang berperilaku pengutamaan terhadap keselamat karena melakukan tindakan represif semata-mata tidak dapat menyelesaikan masalah keselamatan jalan.